2018
DOI: 10.2147/copd.s163243
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of bronchiectasis in emphysema-predominant COPD patients

Abstract: BackgroundCOPD has been identified as an etiology or related disease of bronchiectasis, and bronchiectasis has been classified as a comorbidity of COPD. In this study, we investigated the prevalence of bronchiectasis in different phenotypes of COPD subjects and the correlation between bronchiectasis and different phenotypes, especially emphysema.MethodsCOPD patients were recruited from April 2012 to December 2015. The presence of bronchiectasis and related information were statistically analyzed. COPD subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
1
25
1
2
Order By: Relevance
“…Of all of these, 14 duplicates were removed. After reviewing the titles and abstracts, 76 full-text articles were identified and reviewed, and, finally, 18 studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in this systematic review and meta-analysis. The flow diagram of article selection according to the PRISMA guideline 13 is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of all of these, 14 duplicates were removed. After reviewing the titles and abstracts, 76 full-text articles were identified and reviewed, and, finally, 18 studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in this systematic review and meta-analysis. The flow diagram of article selection according to the PRISMA guideline 13 is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 415,257 subjects with COPD from 18 observational studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were eligible for this meta-analysis, and bronchiectasis was present in 25,929 subjects (6.24%). The sample size ranged from 54 to 386,646, and 6 studies [17][18]20,22,25,33 had a small population (N < 100).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…COPD often coexists with other diseases (comorbidities) which may have significant impacts on prognosis of COPD patients. With increasing use of high-resolution computed tomography (HRCT) in assessment of COPD, a high prevalence of previously undiagnosed bronchiectasis was found in COPD patients, ranging from 8.1-69% [7][8][9][10][11][12][13][14][15][16][17][18][19]. Some previous studies suggested the presence of bronchiectasis predicted worse outcome of COPD patients [9-11, 13, 15, 20].Therefore, bronchiectasis was proposed as one of COPD comorbidities by 2014 global initiative for chronic obstructive lung disease (GOLD).…”
mentioning
confidence: 99%